Expression of Vascular Endothelial Growth Factor Receptor Increases in Fetal Liver after Administration of High Doses of Vitamin A to Pregnant Mice - Sabahat Zulfiqar, Shumaila Shakoor, Bahadur Baloch, Rahat Bano Siddiqui, Rabia Latif, Uruj Zehra (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin A belongs to an array of retinoids, which have a pivotal part in the development of embryo and fetus and is important in themorphogenesis and cellular differentiation of developing liver. Vascular endothelial growth factor (VEGF) and its receptor the vascular endothelial growth factor receptor 2 (VEGFR2) are known to regulate the formation of vasculature and organogenesis of liver. For the contribution of better enlightenment of the modulating effects of vitamin A on the developing liver we investigated the effect of vitamin A on the histology and immunohistochemical expression of VEGFR2 in the liver from the fetuses. Methods: For this purpose, eighteen pregnant albino mice were divided into three groups having six mice each. Group A served as control and was given 1ml of olive oil whereas group B and C were experimental groups and were given 0.6mg/kg and 1.8mg/kg of vitamin A diluted in 1ml of olive oil. Doses were given at 7th, 8th and 9th gestational days (GD). All animals were sacrificed at 18th GD and the livers from the fetuses were collected to observe the histological parameters such as inflammation, hepatic vacuolar degeneration, central vein diameter and hemorrhage in central veins along with immunohistochemical expression of VEGFR 2. Results: Results showed that vitamin A affected the histology of liver. Inflammation, hepatic vacuolar degeneration (HVD) and the central vein hemorrhages were increased significantly (p<0.001), while diameter of the central vein decreased (p<0.001) in group C as compared to group A and B. The immunohistochemical expression of VEGFR2 decreased in sinusoids of group C (p<0.001) as compared to group A and B. Conclusion: Thus, the maximum tolerated dose of vitamin A given to group C tends to affect the microarchitecture of the developing liver and expression of VEGFR2. Keywords: Vitamin A, Vascular endothelial growth factor, VEGF, vascular endothelial growth factor receptor 2,